Beyond BRCA Status: Clinical Biomarkers May Predict Therapeutic Effects of Olaparib in Platinum-Sensitive Ovarian Cancer Recurrence - Nakanishi, Kazuho; Yamada, Takashi; Ishikawa, Gen; Suzuki, Shunji (Frontiers in Oncology, 2021)
The purpose of this study was to investigate the predictors of the effect of olaparib on platinum-sensitive recurrent ovarian cancer with unknown germline BRCA mutations. We retrospectively examined 20 patients with platinum-sensitive ovarian cancer who were treated at the Nippon Medical School Chiba Hokusoh Hospital, Japan, from 2018 to 2020. We found that the median progression-free survival was 11.4 months (95% Confidence interval (CI): 3.8–Not Available (NA)) in the group with NLPN score [recurrent neutrophil-lymphocyte ratio (rNLR) × number of previous regimens] >7.51, and median progression-free survival was not reached in the group with NLPN score <7.51 (95% CI: 21.8–NA) (p = 0.0185). There was a clear correlation between the degree of dose reduction of olaparib and recurrence (p = 0.00249). Our results show that NLPN scores lower than 7.51 are associated with a favorable outcome of olaparib treatment for platinum-sensitive recurrent ovarian cancer. In cases with a high rNLR, it may be necessary to start olaparib treatment as early as possible to obtain low NLPN scores. Our results imply that the effectiveness of olaparib can be determined after recurrence and before platinum treatment begins. As newer drugs for ovarian cancer are developed, the measurement of biomarker levels at the start of treatment for recurrent ovarian cancer, as shown in our study, may provide strong support for cancer treatment protocols.